INDONESIAN-ENGLISH CODE MIXING IN RIA SW'S VIDEO BLOG - Elita Ulfiana (UIN Raden Mas Said Surakarta, 2021)
Video blogs or vlogs are stories of someone’s daily life visualized and uploaded via YouTube. It managed to increase the most video uploads on YouTube. To attract the sympathy of the audience, the use of informal language or a relaxed variety was chosen to be more communicative. The data in this study were taken from Ria SW’s vlog, one of the food vloggers with 2,700 subscribers. The use of two languages, Indonesian and English, turned out to attract and represent young people who are slang and intellectual speakers. Using two languages at once or referred to as code mixing, is a linguistic phenomenon that needs to be responded to using sociolinguistic theory to find forms of code-mixing in Ria SW’s vlog.The method used in this research was a qualitative method. Through these methods and theories, it can be seen that RiaSW’s use of Indonesian code-mixing. The type of code-mixing used by Ria SW is external code-mixing. The form of external code-mixing reflects the existence of high intellectual abilities and exudes moderate values. The form of code-mixing used is in the form of words, phrases and repetitions. The use of word types in code-mixing expressed by Ria SW is in nouns, verbs, and adjectives. The use of the noun form tended to mention the name of places and foods. The use of the verb form tended to invite, while the use of the adjective serves to explain the taste of the food. The causes of this communication strategy, the use of code-mixing in Ria SW’s vlog are to get good communication by using more popular terms and letting the viewers understand the speaker code and the foreign terms of the tourism sector.